The Students' Difficulties in Speaking-English Performance at a Public Senior High School in Amurang - Kondo, Petrus; Ratuwongo, Putri (DIDASCO, 2023)
The ability to speak English fluently and confidently opens up various opportunities, both academically and professionally. However, many students face difficulties in speaking English, which can hinder their overall language development and communication skills. This study aimed to describe students the level for each type of difficulties in speaking English. In addition to that, this study also wanted to describe the factors that had the highest score of difficulties in speaking English. The research design was descriptive quantitative method. The data were analysed by using descriptive analysis to find the mean score. Fifty-five respondents were selected by using simple random sampling. The instrument was 24-items questionnaire adapted from Turkey Ozkan (2020). The findings of this showed that public high school students of Amurang possess difficulties with the score mean of these are as lack of vocabulary (3.70), ungrammatical words (3.52), poor pronunciation (3.57), lack of confidence (3.42), and fear of making mistakes (3.62). Lack of vocabulary, ungrammatical words, poor pronunciation and fear of making mistakes were all interpreted as high difficulties and lack of confidences was interpreted as moderate difficult. The senior high school students of Amurang possess the highest difficult in lack of vocabulary. Thus, incorporating more speaking activities in the classroom and providing opportunities for regular practice can help students overcome their fear of speaking.